Health Care Engagement and Follow-up After Perceived Discrimination in Maternity Care. Issue 9 (September 2017) - Attanasio, Laura; Kozhimannil, Katy B.
Abstract : Background: Negative experiences in the health care system, including perceived discrimination, can result in patient disengagement from health care. Four million US women give birth each year, and the perinatal period is a time of sustained interaction with the health care system, but potential consequences of negative experiences have not been examined in this context. We assessed whether perceived discrimination during the birth hospitalization were associated with postpartum follow-up care. Methods: Data were from the Listening to Mothers III survey, a nationally drawn sample of 2400 women with singleton births in US hospitals in 2011–2012. We used multivariate logistic regression to estimate adjusted odds of having a postpartum visit in the 8 weeks following birth by perceptions of discrimination due to (1) race/ethnicity; (2) insurance type; and (3) a difference of opinion with a provider about care. Results: Women who experienced any of the 3 types of perceived discrimination had more than twice the odds of postpartum visit nonattendance (adjusted odds ratio=2.28, P =0.001), after adjusting for socioeconomic and medical characteristics. Conclusions: The postpartum visit is an opportunity for a patient and clinician to address continuing health problems following birth, discuss contraception, and screen for chronic disease. Forgoing this care may have negative health effects. The findings from this study underscore the need to reduce discrimination and improve maternity care experiences.